2019
DOI: 10.2139/ssrn.3360483
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Financially Illiterate Groups: An International Comparison

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Based on the results it can be stated that although young adults differ from older generations in a number of aspects regarding financial attitudes and behaviour, they themselves form a quite heterogeneous group. This statement is in accordance with findings of Sinha et al (2018) or De Beckker et al (2019, who also emphasize the importance of different groups in the same age-group. We may further deepen the picture and knowledge about them if we divide them into smaller groups, thus, create segments.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the results it can be stated that although young adults differ from older generations in a number of aspects regarding financial attitudes and behaviour, they themselves form a quite heterogeneous group. This statement is in accordance with findings of Sinha et al (2018) or De Beckker et al (2019, who also emphasize the importance of different groups in the same age-group. We may further deepen the picture and knowledge about them if we divide them into smaller groups, thus, create segments.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study confirm the generally low level of financial literacy found in most other studies, especially in France. This problem has been recurrent for a long time (De Beckker et al, 2019;Xiao and Porto, 2017). Thus, since 2002, the OECD has officially recognized the importance of financial education through the launch of a dedicated global project.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that might impact the results was the financial literacy of our sample. Recent studies suggest that the higher the literacy the more financial products the person holds [De Beckker et al, 2019] and that the family is the key variable in the development of such skills [Mancebón et al, 2019]. It would require more research to find out whether financial literacy is the moderator of a relation between various brand narratives and brand associations in such product category, as it was found to moderate a relation between financial education and sound personal finance [Son and Park, 2019].…”
Section: Discussionmentioning
confidence: 99%